Biden's choice and FDA's loosening standards of evidence. (23rd March 2021) - Lenzer, Jeanne
Abstract : The US Food and Drug Administration is widely considered the world's premier regulator of drugs and devices, but critics say three decades of deregulation have resulted in increasingly lax oversight and lower standards of evidence, writes Jeanne Lenzer